Health Education in Context: An International Perspective on Health Education in Schools and Local Communities
VII, 278 p.
Keywords: This book presents an international perspective on health education and specifically the influence that context has on this aspect of education. The focus includes both formal and non-formal health education and the factors that impact upon its effectiveness, particularly in non-Western and non-English-speaking contexts (i.e., outside the UK, USA, Australia, NZ, etc.). An important feature of the book is that it draws upon the experiences and research of local experts, representing the perspectives of an extremely diverse cohort across the world (22 countries and 2 regions in total). The book addresses topics such as: the development and implementation of health education in different countries; the influence of political, cultural, societal or religious mores; governmental or ministerial drives; economic or other pressures driving curriculum reform; and the influence of external assessment regimes on health education. By embedding discussions of health education in local contexts and representing a diversity of perspectives on this important topic this book highlights both barriers and enablers to improving health education across the globe.